2013
DOI: 10.1002/nag.2161
|View full text |Cite
|
Sign up to set email alerts
|

A stabilized assumed deformation gradient finite element formulation for strongly coupled poromechanical simulations at finite strain

Abstract: An adaptively stabilized finite element scheme is proposed for a strongly coupled hydro-mechanical problem in fluid-infiltrating porous solids at finite strain. We first present the derivation of the poromechanics model via mixture theory in large deformation. By exploiting assumed deformation gradient techniques, we develop a numerical procedure capable of simultaneously curing the multiple-locking phenomena related to shear failure, incompressibility imposed by pore fluid, and/or incompressible solid skeleto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
144
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 113 publications
(152 citation statements)
references
References 50 publications
2
144
0
Order By: Relevance
“…3.4 for cohesionless granular media, the pore geometry evolves when subjected to external loading. While continuum-based numerical models, such as [65,67], often employ the size of the void space to predict permeability, the anisotropy of the effective permeability is often neglected. Certainly, this treatment may lead to considerable errors in the hydromechanical responses if the eigenvalues of the permeability tensor are significantly different.…”
Section: Effective Permeabilitymentioning
confidence: 99%
“…3.4 for cohesionless granular media, the pore geometry evolves when subjected to external loading. While continuum-based numerical models, such as [65,67], often employ the size of the void space to predict permeability, the anisotropy of the effective permeability is often neglected. Certainly, this treatment may lead to considerable errors in the hydromechanical responses if the eigenvalues of the permeability tensor are significantly different.…”
Section: Effective Permeabilitymentioning
confidence: 99%
“…Mitigating procedures based on linear interpolation with bubble functions are, however, not suited for explicit dynamic applications [24]. Sun et al [27] provide an assumed deformation gradient formulation for poro-mechanical problems to mitigate the locking associated with incompressibility. It is also shown that spurious pore pressure modes can be filtered out via a penalty formulation.…”
Section: Alternative Stabilizing Proceduresmentioning
confidence: 99%
“…The approach is rooted more in the physics rather than in the mathematics. Rigorous mathematical expositions, in which the inf-sup condition is addressed, can be found in references [19,27], with Dvorkin [14] interpreting the inf-sup condition from an engineering perspective.…”
Section: Alternative Stabilizing Proceduresmentioning
confidence: 99%
“…Separate numerical techniques to treat this extra source of incompressibility are required, and they have been addressed in models using the reduced u − p w formulation. Sun et al() proposed a formulation with an assumed deformation gradient that has the F‐bar method as a limiting case. Monforte et al examined three‐field mixed formulations in which either the effective pressure or the Jacobian was added as supplementary nodal variables and stabilization techniques were employed in all scalar equations.…”
Section: Introductionmentioning
confidence: 99%